Unfamiliar Connections: Special Forces and Paramilitaries in the Former Yugoslavia. Issue 1 (2nd January 2016) - Horncastle, James
Abstract : The study of special forces is dominated by accounts of British and American units. This article, using the case study of the Yugoslav Special Forces in the 1990s and early 2000s, demonstrates how units that developed outside the Anglosphere possess not only a different military function but also distinct cultures and structures. Therefore, when analyzing units that develop outside the Anglosphere, we need to consider new analytical tools and approaches.